The Quiet Eye: Origins, controversies, and future directions - Vickers, J. N. (Kinesiology Review, 2016)
Article provides an overview of motor tasks in which QE studies have been completed. The categorization is based on how participants control their QE and not on their physical movements, which uses a different taxonomy. Next, it provides a brief overview of the main characteristics of targeting, interceptive timing tasks, and QE training studies. In targeting tasks, the function of the QE and attention system is to locate a target in space and control the aiming of an object to a specific target area. In these tasks an object is propelled with the hands or feet away from the body in an aiming movement toward a target (Vickers, 2007). Accuracy and consistency in performance are the ultimate goal in tasks such as shooting a basketball, performing a golf putt, throwing a dart, shooting a rifle or bow, or throwing to a receiver. Although the motor behaviors differ markedly in each case, the problem for the gaze and attention system is the same: to focus on the most critical part of the target and acquire specific information so that there is an optimal coupling between the gaze and aiming movements, thus leading to successful completion of the task. The ability to accurately select the correct cues for movement is crucial for successful performance, as is perception-action coupling, which is the ability to gain the information needed prior to a critical phase of the movement. The additional time needed for a longer QE duration is most often accomplished by having an earlier QE onset, before the critical movement.